The Influence of Motivational Leadership and Compensation on Employee Performance Results in Mojokerto City - Rini Andita; Hasan Ubaidilah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to explain the variables of leadership, motivation, and compensation on employee performance either partially or simultaneously. This research is based on the facts that exist in the field that leadership has a significant effect on employee performance results while the compensation variable has no significant effect on employee performance results, while employee internal motivation has more influence on employee performance. The method used in this research is descriptive quantitative technique. By using interview techniques and distributing questionnaires to 56 employees of the Mojopahit Mojokerto public drinking water company as a data collection technique. The data analysis technique used in this study is to use multiple linear regression analysis techniques. The results of this study state two conclusions, namely: first, leadership partially affects employee performance, motivation affects employee performance results. While compensation has no effect on the results of employee performance. Second, simultaneously, the variables of leadership, motivation and compensation have an effect on employee performance.